Superovulation of acyclic crossbred heifers - CHOUDHARY, FATEH LAL; DEEN, AMINU; SHARMA, S S; SINGHRATHORE, JIVRAJ; SARASWAT, PRADEEP; ARORA, ASHUTOSH (The Indian Journal of Animal Sciences, 2013)
The study was conducted on 4 crossbred heifers, each of which were induced to superovulate twice at suitable period of interval alternately with 1 of the 2 treatments. Treatment group -A (n = 4) comprised controlled internal drug release (implant contains 1.9 g (progesterone) vaginal implant for 9 days plus 75 units NIH standard FSH administered in 6 equally divided doses at 12 hr intervals on days 7, 8 and 9 of the implant (implantation day = day 0). The implant was with drawn at the time of fifth injection ofFSH. Treatment group - B (n = 4) was same as A except that 1000 IU PMSG was also administered on day sixth in addition to vaginal implant and FSH. Rectogenital palpation revealed that 3/4 animals responded in both the treatment groups. One animal did not respond and developed polycystic ovaries after group - A treatmenr. All the 3 animals of group -A and 2/3 animals of group -B yielded 20 and 23 embryos/ova, respectively. The 20 embryos/ova of group -A included 4 retarded, 6 morulae and 10 compact morulae, of which 2, 4, 5, 5 and 4 were graded as excellent, good, fair, poor and retarded, respectively. The 23 embryos/ova of group-B included 4 unfertilized, 8 morulae, 2 compact morulae and 9 blastocysts, of which 17,2 and 4 were graded as good, fair and retarded/unfertilized, respectively. Superovulation response and total embryo recovery did not decline after repeated treatment but the average quality of embryos produced after repeated superovulation was inferior. Unfertilized, fragmented and retarded embryos/ova were recovered after repeated treatments only. Many of the embryos produced out of repeated treatment were sticky. These findings gave an indication that inferior quality of embryos after repeated superovulation might be due to subclinical endometritis.